PENILAIAN ASET DAN KEWAJIBAN PT CEMARU LESTARI DALAM RANGKA REORGANISASI KUASI TAHUN 2011 - , Achmad Faisal Siregar, B.A.; , Dr. Wakhid Slamet Ciptono, MBA., MPM., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The objective of this research was to estimate the value of assets and liabilities of PT Cemaru Lestari associated with Quasi Reorganization in 2011 using asset-based approach with adjusting book value method. The Analysis of Adjusted Book Value (ABV) methods is to make adjustments to the book value of the audited financial statements which intended to reflect its market value. Appropriate approach to the valuation of its assets and liabilities are highly dependent on its characteristics. The data used consist of